Local and External Stakeholders Affecting Educational Change during the Coronavirus Pandemic: A Study of Facebook Messages in Estonia - Piret Luik; Marina Lepp (MDPI AG, 2021)
Education worldwide was affected by the coronavirus pandemic when many countries, including Estonia, had to switch to distance learning. It was an unexpected change in education and required a response from relevant stakeholders. This study aims to understand the activities of different stakeholders as revealed in the messages of the Facebook group 'Homeschooling with technology' from 6 March to 26 April 2020. A mixed method study design was used, including quantitative and qualitative content analysis of 872 messages posted by members of the Facebook group, which were divided into eight role groups. Teachers, educational technologists, principals and parents represented local stakeholders while external stakeholders included members from government institutions, supporters, teacher educators and members with other roles. The analysis covered activeness of each role group, emotional expressions, speech acts and topics represented in messages. The results indicate that educational technologists played a key role in handling the coronavirus pandemic situation in education. However, local stakeholders also received support from external stakeholders. The results help capture the roles, experiences and views of different stakeholders during the educational change caused by the coronavirus pandemic in order to learn from this and to be prepared for such situations in the future.